Antifungal activity and brine shrimp toxicity assessment of Bulbine abyssinica used in the folk medicine in the Eastern Cape Province, South Africa (Bangladesh Journal of Pharmacology, 2016)
Bulbine abyssinica is widely used in folk medicine in Eastern Cape Province, South Africa. The aim of this study was to evaluate the antifungal and toxicity potentials of essential oil, acetone and aqueous extracts of this species using standard procedures and brine shrimp test, respectively. The results showed that the species was active against the growth of Microsporum canis, Microsporum gypseum and Trichophyton rubrum among the evaluated opportunistic fungi. The toxicity results showed that the lowest cysts hatching success was observed with the essential oil, then acetone extract, with aqueous extract exhibiting the highest hatching success. Based on the criterion of toxicity indices of the lethality test, all the plant fractions exhibited LD50 values greater than 1 mg/mL hence are non-toxic. These findings indicate that B. abyssinica is a good source of antifungal agents.